2021
DOI: 10.1186/s12877-021-02301-y
|View full text |Cite
|
Sign up to set email alerts
|

The PROMOTe study: targeting the gut microbiome with prebiotics to overcome age-related anabolic resistance: protocol for a double-blinded, randomised, placebo-controlled trial

Abstract: Background Loss of skeletal muscle mass and strength occurs with increasing age and is associated with loss of function, disability, and the development of sarcopenia and frailty. Dietary protein is essential for skeletal muscle function, but older adults do not anabolise muscle in response to protein supplementation as well as younger people, so called ‘anabolic resistance’. The aetiology and molecular mechanisms for this are not understood, however the gut microbiome is known to play a key ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…A few studies have been conducted to examine the effects of prebiotics on skeletal muscle mass and muscle strength through changing gut microbiota [121]. A study in elderly human subjects evaluated the effects of consuming a prebiotic supplement consisting of inulin and fructooligosaccharide, which would be expected to promote a healthy microbiome [122,123]. They reported that the subjects having the prebiotic had greater hand strength and endurance than control subjects, although they did not report the effects on the microbiome [122,123].…”
Section: Probiotic and Prebiotic Intakes Gut Microbiota And Skeletal ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have been conducted to examine the effects of prebiotics on skeletal muscle mass and muscle strength through changing gut microbiota [121]. A study in elderly human subjects evaluated the effects of consuming a prebiotic supplement consisting of inulin and fructooligosaccharide, which would be expected to promote a healthy microbiome [122,123]. They reported that the subjects having the prebiotic had greater hand strength and endurance than control subjects, although they did not report the effects on the microbiome [122,123].…”
Section: Probiotic and Prebiotic Intakes Gut Microbiota And Skeletal ...mentioning
confidence: 99%
“…A study in elderly human subjects evaluated the effects of consuming a prebiotic supplement consisting of inulin and fructooligosaccharide, which would be expected to promote a healthy microbiome [122,123]. They reported that the subjects having the prebiotic had greater hand strength and endurance than control subjects, although they did not report the effects on the microbiome [122,123]. Vegan diets rich in dietary fibers are associated with rich Prevotella and high microbial diversity, and Prevotella has been associated with high-carbohydrate and high-fiber diets [70].…”
Section: Probiotic and Prebiotic Intakes Gut Microbiota And Skeletal ...mentioning
confidence: 99%
“…It is known that older people present an 'anabolic resistance', that is, the inability to anabolize muscle in response to protein supplementation. The modulation of the gut microbiome using a prebiotic, in addition to protein supplementation, can improve muscle strength supplementation alone [102], suggesting new aids to mitigate sarcopenia and frailty in older adults.…”
Section: Prebioticsmentioning
confidence: 99%
“…Those who take prebiotic and protein supplements have a greater improvement in muscle strength than those who take protein supplements alone. 137 …”
Section: Approaches For Bacteriotherapy: Probiotics Prebiotics and Synbioticsmentioning
confidence: 99%